LEGAL FUTSAL : DESIGNING THE FUTURE THROUGH SPORT AS SOCIAL INCLUSION TOOL IN THE MUNICIPALITY OF CACERES -MT (Fiep Bulletin - online, 2016)
The Futsal legal, social sports project aims to act preventively with the children at social risk, arising from minimum income family, a complementary action of the School. Aiming, oportunizar children, conditions necessary to develop their potential to the process of self-realization and exercise full citizenship through sports activities, specifically futsal, and issues related to health and quality of life, promoting the involvement and cooperation. And IFMT Campus Cáceres, through the sport as a great tool for transformation and social inclusion, developed with students aged 08-10 years selected through records of entries made in the school units from surrounding neighborhoods IFMT - Campus Cáceres taking priority students who participate in programs of the Federal Government. Students included in the Project participate in anthropometric, physical and technical, initial and periodic evaluations in order to perform the initial diagnosis, monitoring of performance and quality of their work, as well as lectures on topics related to health and quality of life issues cultural relations between the media and sport, violence and sport, and food, in addition to monitoring school performance. The Futsal Legal Project aims to achieve specifically, and the development and learning of the sport in question, the promotion of health and physical fitness, purchasing habits and motor behaviors, and understanding of sports as a cultural factor, stimulating feelings of solidarity , cooperation, autonomy and creativity. The important results, refer to the improvement of family relationships, significant improvement in school learning, as well as the improvement of the motor and emotional development, and automatically improving the quality of life.
Keywords: Physical Education; Sport; Sports Initiation